Multicomponent Intervention for Patients Admitted to an Emergency Unit for Suicide Attempt: An Exploratory Study - Brovelli, Sebastien; Dorogi, Yves; Feiner, Adam-Scott; Golay, Philippe; Stiefel, Friedrich; Bonsack, Charles; Michaud, Laurent (Frontiers in Psychiatry, 2017)
Suicide is a major cause of premature deaths worldwide and belongs to the top priority public health issues. While suicide attempt is the most important risk factor for completed suicide, intervention for suicide attempters (SA) have produced mixed results. Since an important proportion of SA request medical care, emergency units (EU) are an opportune setting to implement such interventions. This exploratory study evaluated the feasibility and acceptability of a multicomponent intervention for suicide attempters admitted to an EU. The intervention consisted of coordination by a case manager of a joint crisis plan, an early meeting with relatives and the existing care network as well as phone contacts during 3 months after suicide attempt. Among 107 suicide attempters admitted to the emergency unit during the study period, 51 could not be included for logistical reason, 22 were excluded and intervention was offered to 34. Of these, 15 refused the intervention, which was thus piloted with 19 SA. First-time attempters most frequently declined the intervention. Feasibility and acceptability of phone contacts and case manager were good, while joint crisis plans and meetings were difficult to implement and perceived as less acceptable. Refusal pattern questions the global acceptability and is discussed: joint crisis plans and meetings will have to be modified in order to improve their feasibility and acceptability, especially among first-time attempters